Osteosarcoma of the mandible in a older woman: a case report - Meireles, Gabriel Menezes; Ferreira, Lais Regina; Araújo, Fernanda Silva; Capistrano, Hermínia Marques; Oliveira, Leandro Junqueira; Lima, Luciano Henrique Ferreira (Journal of Oral Diagnosis, 2022)
Osteosarcoma is a malignant tumor with mesenchymal origin, most commonly found in extremities, pelvis and axial skeleton, including only 6% with mandibular and maxillary involvement. In jaws, this lesion is, generally, a single lesion with predilection for posterior ramus mandible and men in the third or fouth decade of life. The aim of this study is report a 57year old woman diagnosed with osteosarcoma in the posterior mandible region treated with surgical resection associated to bone and soft tissue reconstructive techniques.